Interactions between serum FSH, inhibin B and antral follicle count in the decline of serum AMH during the menstrual cycle in late reproductive age - Robertson, David M. (Endocrinol Diabetes Metab, 2020)
OBJECTIVE: To investigate the hormonal interrelationships during the menstrual cycle in women of late reproductive age with suppressed serum AMH and antral follicle count (AFC). METHODS: Serum hormones (AMH, FSH, LH, estradiol, progesterone, inhibin A, inhibin B), AFC (2‐10 mm) and AMH/AFC ratio (an estimate of AMH/follicle) were assessed every 2‐3 days across the menstrual cycle in 26 healthy ovulatory women aged 18‐50 years. RESULTS: An 11‐fold fall in AMH/AFC was observed in women aged ≥45 years compared to those 18‐45 years (P < .001). Although women ≥45 years exhibited normal menstrual cycle patterns of serum estradiol, progesterone, LH and inhibin A, FSH was elevated (P < .001) and inhibin B suppressed (P < .001) compared to the younger group. Overall FSH was inversely correlated (r = .55, P < .05) and AMH directly correlated (r = .88, P < .01) with AFC; however, these relationships were curvilinear and more pronounced when AFC was low. Inhibin B was directly linearly correlated (r = .70, P < .01) with AFC across both high and low AMH/follicle groups. CONCLUSIONS: It is hypothesized that the marked fall in AMH/follicle in late reproductive age is attributed to the change in the hormonal interplay between the pituitary and ovary. The fall in AFC leads to a decrease in inhibin B and a concomitant increase in FSH by a recognized feedback mechanism. It is postulated the elevated FSH suppresses AMH either directly or indirectly through oocyte‐specific growth factors leading to a marked fall in AMH/follicle. We propose that pituitary‐ovarian and intra‐ovarian regulatory systems underpin the accelerated fall in AMH/follicle during the transition to menopause.